Preventive and Protective Properties of Zingiber officinale (Ginger) in Diabetes Mellitus, Diabetic Complications, and Associated Lipid and Other Metabolic Disorders: A Brief Review. (22nd November 2012) - Li, Yiming; Tran, Van H.; Duke, Colin C.; Roufogalis, Basil D.
Abstract : Zingiber officinale (ginger) has been used as herbal medicine to treat various ailments worldwide since antiquity. Recent evidence revealed the potential of ginger for treatment of diabetes mellitus. Data from in vitro, in vivo, and clinical trials has demonstrated the antihyperglycaemic effect of ginger. The mechanisms underlying these actions are associated with insulin release and action, and improved carbohydrate and lipid metabolism. The most active ingredients in ginger are the pungent principles, gingerols, and shogaol. Ginger has shown prominent protective effects on diabetic liver, kidney, eye, and neural system complications. The pharmacokinetics, bioavailability, and the safety issues of ginger are also discussed in this update.